Pengaruh Pemberian Vermikompos dan PGPR terhadap Pertumbuhan dan Kadar Gula Semangka (Citrullus vulgaris) - Dido Ari Widodo; Juli Santoso; Nora Augustien Kusumaningrum (G-Tech: Jurnal Teknologi Terapan, 2024)
Watermelon plants are one of the commodities in Indonesia and have high economic appeal. Efforts to increase plant growth and yield continue to be made, one of which is using vermicompost and PGPR. This research was conducted to determine the correct dose of vermicompost and PGPR concentration to increase the growth and yield of watermelon plants. The research used a 2-factor Completely Randomized Design. The first factor is the dose of vermicompost (0, 100, 150 and 200 grams of vermicompost). The second factor is the PGPR concentration (0, 15, 20 and 25 ml/l). The results of the research showed that there was an interaction between vermicompost and PGPR on plant length at 42 and 49 HST and the sugar content. The single factor of vermicompost had a significant effect on plant length aged 21, 35, 42 and 49 HST and stem diameter aged 14 to 49 HST.